Sizing of Photovoltaic Wind Battery system integrated with Vehicle-To-Grid using Cuckoo Search Algorithm - Alsharif A.; Tan C.W.; Ayop R.; Lau K.Y.; Toh C.L. (Institute of Electrical and Electronics Engineers Inc., 2023)
Charging (batteries); Electric power transmission networks; Energy management; Energy management systems; Hybrid systems; Learning algorithms; Optimization; Secondary batteries; Vehicle-to-grid; Vehicles; Cuckoo search algorithms; Economic system; Low-costs; Metaheuristic optimization; Photovoltaics; Power; REF; Renewable energy source; Vehicle to grids; Wind-battery systems; Renewable energy resources